Development of 3-D display technologies - Ng, Desmond Jun Han (Nanyang Technological University, 2020)
Many research has been done in recent years on 3D LED cube display. This project will focus on the design and development of a 3x16x12 3D LED display. This report document the creation of a functional 3D LED display using commercially available parts such as the WS2812D RGB LEDs as well as open-source software like the FastLED libraries to control the LED cube. The limitation of the currently available LED Cube as well as the proposed solution is discussed in this report. The limitation and future implementations are also further discussed.